The Role of Public Relations Management in Building a School’s Brand: Peran Manajemen Hubungan Masyarakat Dalam Membangun Branding Sekolah - Fatimah, Siti; Haryanto, Budi (Indonesian Journal of Innovation Studies, 2026)
General Background: Public relations management serves as a critical strategic instrument for institutional sustainability and reputation management in modern educational organizations. Specific Background: Building a distinct school brand requires structured public relations strategies to manage internal collaboration, digital communication channels, and community engagement in Islamic junior high schools. Knowledge Gap: However, empirical analyses examining integrated public relations operational strategies alongside specific institutional challenges within Islamic-based schools remain limited. Aims: This study evaluated the strategic role and supporting factors of public relations management in developing school branding at SMPIT Imam Bukhari using a qualitative case study approach. Results: The findings demonstrate that public relations builds institutional image through active publication, program promotion, and stakeholder mediation, supported by solid internal collaboration, digital optimization, parent involvement, and unique identities such as Tahfizh Al-Qur'an. Novelty: This study establishes an operational public relations framework integrating Islamic educational identity with digital stakeholder management. Implications: Educational administrators can implement these communication strategies to strengthen parental trust, overcome institutional communication barriers, and enhance school competitiveness. Key Findings Highlights Public relations functions strategically through structured publication, event promotion, and stakeholder mediation to reinforce educational reputation. Internal synergy, digital media optimization, active parental involvement, and distinctive religious identities drive successful institutional branding. Communication centralization among homeroom teachers and digital skill gaps represent primary operational challenges in school public relations management. Keywords: Public Relations Management, School Branding, Positive Image, Islamic Educational Institutions, Stakeholder Engagement